Analisis Kesehatan Bank Syariah Indonesia (BSi) Tahun 2023 Menggunakan Metode Risk Based Bank Rating (RBBR) - Wahab, Ikfina Yamaulanan Nuzula; Safitri, Ainun; Ekaningsih, Lelyana Ferawati (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2025)
This study aims to analyze the financial health of Bank Syariah Indonesia (BSI) in 2023 using the RBBR (Risk Based Bank Rating) method. Secondary data from BSI's annual financial reports were used in this research. The analysis results show that BSI has an excellent risk profile with a Non-Performing Financing (NPF) of 0.55% and a Financing to Deposit Ratio (FDR) of 81.73%. The implementation of corporate governance is also rated as sound. BSI's earnings performance is very good, with a Return on Assets (ROA) of 2.35%, a Return on Equity (ROE) of 16.88%, and a Net Operating. Margin (NOM) of 2.58%. Additionally, BSI's capital adequacy is very high, with a Capital Adequacy Ratio (CAR) of 21.04%. The conclusion of this study is that BSI showed excellent performance in 2023, reflecting effective risk management, good corporate governance, high earning ability, and adequate capital sufficiency. The implication of this research indicates that BSI has a strong position in the Islamic banking industry and is well-prepared to face future challenges. It is recommended for future research to conduct long-term analysis and consider external factors affecting the bank's performance